Radiology Service Tariff Calculation Model Using the Activity Based Costing (ABC) Method at Naibonat Regional Hospital, Kupang Regency - Simeon Alfredo Tabe Doa; Leny Latifah; Siti Masrochah (International Journal Labs, 2023)
Determination of health service tariffs also determines optimal health service outcomes. Determination of radiology examination rates at Naibonat Hospital until 2023 still refers to Regional Regulation No. 5 of 2012 concerning public service fees, where the determination of fees still uses the conventional calculation system, and there are changes in image processing modalities, tools, and materials used, this demands a rate adjustment. Calculation of rates using the Activity Based Costing (ABC) method, can be a solution to determine more accurate rates, supported by Pramawati's research (2021) which shows the results of determining rates are more accurate using the ABC method. The purpose of this study was to calculate the tariff pattern for radiological examinations at Naibonat Hospital using the ABC method and obtain an accurate tariff calculation model for radiological examinations. This research is a descriptive explorative study, with a quantitative approach using numerical data which aims to calculate a unit cost-based examination rate model by implementing an Activity Based Costing system on ultrasound examination of the abdomen, chest x-rays, abdomen, skull, and extremities. The data obtained was then subjected to qualitative analysis to obtain the steps for calculating tariffs using the ABC method. The results of this study indicate that the calculation model for radiological examination rates using the ABC method is valid. To find rates, first, determine the basic rate with the formula unit cost = direct cost + overhead, the results obtained are then calculated. Examination rates = cos unit + hospital services, so the examination rates at the Radiology unit of Naibonat Hospital, namely abdominal USG Rp 242.036, photo thorax Rp. 116,995, photo abdomen Rp. 150,321, photoskull Rp. 153,262, and a photo extremity Rp. 121,409.